A novel Turkish instrument for assessing quality of life in chronic otitis media - translation and validation of Zurich chronic middle ear inventory - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2020)
Background/aim: The Zurich Chronic Middle Ear Questionnaire (ZCMEI-21) is a newly-developed German-language questionnaire. The purpose of this study was to analyze the quality of life (QoL) of chronic otitis media (COM) patients and translate, transculturally adapt, and validate the ZCMEI-21 into Turkish. Materials and methods: Based on internationally accepted guidelines, the ZCMEI-21 was translated into Turkish. To assess its validity, the total score of the ZCMEI-21-Tur was compared to the scores taken from the original validation study and a question that was directly related to the health-related QoL (HRQoL), as well as the general criterion EQ-5D-5L. Questionnaires were completed by healthy volunteers and the results were evaluated statistically. Results: A total of 80 COM patients and 40 healthy volunteers were prospectively enrolled in this study. Regarding internal consistency, the questionnaire showed a Cronbach a of 0.94, which indicated high internal consistency. Moreover, internal consistency was also determined to be excellent for the Cronbach a of the individual subscales, as follows: car sign symptoms, 0.79; hearing, 0.83; psychosocial impact, 0.91, and medical resources, 0.84. Conclusions: The ZCMEI-21 was translated into Turkish and validated. Therefore, the ZCMEI-21-Tur was suitable for use in assessing HRQoL in adult patients with COM.
Keywords: ZCMEI-21; chronic otitis media; quality of life; Turkish; REPORTED OUTCOME MEASURES; HEALTH